Deteksi Coxiella burnetii pada Sapi Kurban Idhul Adha di Cimanggu, Kabupaten Bogor Tahun 2015-2016 (DETECTION OF COXIELLA BURNETII IN IED AL-ADHA SACRIFICIAL COW IN CIMANGGU, BOGOR REGENCY AT 2015-2016) - Untari, Handayu; Setiyono, Agus; Handharyani, Ekowati; Padaga, Masdiana C. (Jurnal Veteriner; Vol 21 No 1 (2020), 2020)
Coxiella burnetii is an intracellular obligate bacterium that causes Q fever disease. Q fever is one of the asymptomatic zoonosis and has a potential as biological weapon. This disease infects much type of animals and has been distributed globally, including in Indonesia. Previous research concluded that West Java is an endemic area of this disease. Bogor in West Java has a potential spread of Q fever disease due to high population of cattle and goat in this region.This study aim was to detect C. burnetii in spleen, lung, kidney, liver and heart of cows. Samples of were taken from a total of 29 sacrificial cows during Eid al-Adha in 2015 and 2016 in the Cimanggu region, Bogor Regency. The examination method used was immunohistochemistry with primary polyclonal antibody Rabbit anti-C. burnetii and HaematoxylineEosine staining. The results of the immunohistochemistry examination showed positive immunoreaction (specific brown color in the cytoplasm of cells) against C. burnetii antibodies respectively in 3 out of 10 samples in 2015 (30%) and 4 out of 19 samples in 2016 (21%). Out of 29 samples, positive immunoreaction were found in lung organ (13,7%) and spleen (10,3%) with variation in changes in histopathological features which include congestion, inflammatory cell infiltration, mucus accumulation, and fibrosis in the lung.